2000
DOI: 10.1211/0022357001773986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lithium on the Pharmacokinetics of Valproate in Rats

Abstract: Combined treatment with lithium and valproate has been used for bipolar disorder. However, the studied interaction between these two drugs has not been fully investigated. We therefore examined the effects of lithium on the pharmacokinetics (plasma disappearance, metabolism and urinary excretion) of valproate in rats. Lithium (2 mEq kg(-1)) was administered intraperitoneally twice a day for ten days. Plasma disappearance curves of valproate (50 mg kg(-1), i.v.), valproate-metabolizing activities of UDP-glucuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…In this study, the pharmacokinetic profiles of single-treatment VPA were similar to the findings of Yoshioka et al31, who showed that soy has a significant effect on the C max of VPA but not on t max value (Figure 1). Analysis of urine excreted 0–24 h after VPA consumption provided a much clearer view of the effect of soy (Figure 2A).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the pharmacokinetic profiles of single-treatment VPA were similar to the findings of Yoshioka et al31, who showed that soy has a significant effect on the C max of VPA but not on t max value (Figure 1). Analysis of urine excreted 0–24 h after VPA consumption provided a much clearer view of the effect of soy (Figure 2A).…”
Section: Discussionsupporting
confidence: 89%
“…The far greater efficacy of simultaneous polytherapy over sequential monotherapies at the same dose is compatible with increasing pharmacoresistance, associated with seizure-induced increases in receptor trafficking, during the delay between sequential drug injections. However, because of the short half-lives of drugs in rats, only 40–50% of injected midazolam would be expected to remain in plasma when valproate is injected (Bittner et al, 2003), and about 60% of injected valproate would be in circulation at the time of ketamine injection (Yoshioka et al, 2000) limiting interactions between sequential drugs. The improvement in outcome when adding low-dose valproate (which was ineffective when given alone) to ketamine and midazolam may reflect the inability of benzodiazepines to fully restore inhibition when treatment is delayed and many synaptic GABA A R are internalized, and the need to enhance inhibition at a non-benzodiazepine site when treatment is delayed and benzodiazepine pharmacoresistance is high.…”
Section: Discussionmentioning
confidence: 99%
“…Blood valproic acid levels were 42 Ϯ 6 mg/l. This level may not reflect the average daily level of valproic acid because the half-life of valproic acid is Ͻ0.5 hr in rats (Yoshioka et al, 2000;Stout et al, 2001).…”
Section: Methodsmentioning
confidence: 98%